Comparison of Signal-to-noise, Blank Determination, and Linear Regression Methods for the Estimation of Detection and Quantification Limits for Volatile Organic Compounds by Gas Chromatography - Sanagi, Mohd Marsin; Ling, Susie L.; Nasir, Zalilah; Hermawan, D.; Wan Ibrahim, Wan Aini; Abu Naim, Ahmedy (2008)
Limit of detection (LOD) and limit of quantification (LOQ) are two important performance characteristics in method validation. This work compares three methods based on the International Conference of Harmonization (ICH) and EURACHEM guidelines, namely, signal-to-noise, blank determination, and linear regression, to estimate the LOD and LOQ for volatile organic compounds (VOCs) by experimental methodology using gas chromatography. Five VOCs, i.e. toluene, ethylbenzene, iso-propylbenzene, n-propylbenzene and styrene, were chosen for the experimental study. The results indicated that the estimated LODs and LOQs were not equivalent and could vary by a factor of 5 to 6 for the different methods. It is therefore essential to have a clearly described procedure for estimating the LOD and LOQ during method validation to allow interlaboratory comparisons.